Fidelización de clientes en la empresa el Mundo de las Llantas en la ciudad de Babahoyo, durante el 2022. - Lascano Vásquez, Abigail Mercedes (2023)
The case study was carried out with the purpose of analyzing the customer loyalty processes that the company "El Mundo De Las Llantas" has during the period 2022, for this, methods, techniques and research instruments were used, such as an interview with the owner and an online survey of the company's customers, which I corroborate with the theoretical development embodied in this study on the lack of strategies or loyalty plan that is not only causing economic losses but also affects the level of competitiveness in the market. In this study you can find possible solutions or recommendations that the business could take into account in order to achieve the customer loyalty plan that the owner wants. Also mentioning that it will be perfected to meet each of the objectives determined the cause and effect of the problem studied.